2012
DOI: 10.1080/10496491.2012.668434
|View full text |Cite
|
Sign up to set email alerts
|

Managing Trade Show Campaigns: Why Managerial Responsibilities Matter?

Abstract: This paper investigated the relationship between managerial responsibilities for important trade show tasks and the marketing performance of trade show marketers. Drawing theoretical insights from organizational role theory and the functionalist perspective of managerial roles, the paper proposed and tested a theory based, multiple task-managerial responsibility linkages using a large b2b trade show as a context. The empirical results indicated that the marketing performance of trade show participants was enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The interviewed managers hold such positions as Marketing Manager, Communications Manager, Marketing & PR Manager and PR Assistant. The choice of informants was in line with the latest research showing that functional managers are fully informed about their companies' trade show campaigns (Tafesse & Korneliussen, 2012a). The interviews took place inside the companies' stands during the press days of the GMS, and were in-depth, each lasting about an hour, and all were audio taped.…”
Section: Methodsmentioning
confidence: 99%
“…The interviewed managers hold such positions as Marketing Manager, Communications Manager, Marketing & PR Manager and PR Assistant. The choice of informants was in line with the latest research showing that functional managers are fully informed about their companies' trade show campaigns (Tafesse & Korneliussen, 2012a). The interviews took place inside the companies' stands during the press days of the GMS, and were in-depth, each lasting about an hour, and all were audio taped.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, complementing Tafesse and Korneliussen (2012), firm managers managers assigned to the event objective setting, selection decision, and implementation should acknowledge the crucialness of foreing events for both marketing and the acquisition of knowledge to innovate. On the other hand, trade shows amplify the positive effect of permanent proximity because attending firms may observe latest trends and novel technologies or engage in collective promotion of their activities (Ramirez-Pasillas, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research in the South Korean market showed that obtaining information for innovation and benchmarking competitors were the most important goals at trade shows (Kalafsky and Gress, 2014). Tafesse and Korneliussen (2012) found a structure model that categorized the items into competitive intelligence, information gathering and image building. Chiou et al (2007) found that relationship management activities are more important for innovative companies.…”
Section: Literature Reviewmentioning
confidence: 99%